Debunking the myth: the involvement of Malaysian retirees in volunteerism - Uttam Singh, Surjit Singh; Md. Sail, Rahim; Abu Samah, Bahaman; Tajudin Shah, Raja Ahmad; Lumayag, Linda Alfarero (Universiti Putra Malaysia Press, 2005)
This is an exploratory study involving the Malaysian retirees from the Premier and Managerial and Professional sectors of the Malaysian Public Service. It examined the extent of the retirees' involvement, motivation and preference in relation to engaging in volunteerism in the country. Methodologically, a mailed-survey questionnaire was conducted to elicit the information and opinion of 261 retirees throughout Malaysia, including Sabah and Sarawak. Based on the findings, these retirees were more than willing to volunteer in religious, social, educational or community type of organization especially to those who needs their expertise. These retirees expressed concerns about the widely-accepted public conditioning that they were no longer productive and could therefore be relegated to the background as far as their relevance was concerned.